Impact of elevated CO2 concentrations on the growth and ultrastructure of non-calcifying marine diatom (Chaetoceros gracilis F.Schütt) - Hanan M. Khairy; Nayrah A. Shaltout; Mona F. El-Naggar; Naglaa A. El-Naggar (Egyptian Journal of Aquatic Research, 2014)
The impacts of different CO2 concentrations on the growth, physiology and ultrastructure of noncalcifying microalga Chaetoceros gracilis F.Schütt (Diatom) were studied. We incubated Ch. gracilis under different CO2 concentrations, preindustrial and current ambient atmospheric concentrations (285 and 385 μatm, respectively) or predicted year-2100 CO2 levels (550, 750 and 1050 μatm) in continuous culture conditions. The growth of Ch. gracilis measured as cell number was decreased by increasing the pCO2 concentration from nowadays concentration (385 μatm) to 1050 μatm. The lowest percentage changes of oxidizable organic matter, nitrite, nitrate, phosphate and silicate were recorded at a higher pCO2 (1050 μatm), and this is in consistence with the lowest recorded cell number indicating unsuitable conditions for the growth of Ch. gracilis. The minimum cell numbers obtained at higher levels of CO2 clearly demonstrate that, low improvement occurred when the carbon level was raised. This was confirmed by a highly negative correlation between cell number and carbon dioxide partial pressure (r = −0.742, p ⩽ 0.05). On the other hand, highest growth rate at pCO2 = 385 μatm was also confirmed by the maximum uptake of nutrient salts (NO3 = 68.96 μmol.l−1, PO4 = 29.75 μmol.l−1, Si2O3 = 36.99 μmol.l−1). Total protein, carbohydrate and lipid composition showed significant differences (p ⩽ 0.05) at different carbon dioxide concentrations during the exponential growth phase (day 8). Transmission Electron Microscopy of Ch. gracilis showed enlargement of the cell, chloroplast damage, disorganization and disintegration of thylakoid membranes; cell lysis occurs at a higher CO2 concentration (1050 μatm). It is concluded from this regression equation and from the results that the growth of Ch. gracilis is expected to decrease by increasing pCO2 and increasing ocean acidification.